Complex Renal Arteriovenous Malformation (AVM) Embolization using Ethylene Vinyl Alcohol (EVOH) Copolymer and a Balloon Microcatheter - Moriarty, Heather Kate; Clements, Warren; Joseph, Tim; Madan, Anoop; Phan, Tuan (Journal of Clinical Interventional Radiology ISVIR, 2019)
Occurrence of a symptomatic renal arteriovenous malformation (AVM) is rare. The authors present the case of a patient with a background of Turner's syndrome, hemophilia B, and horseshoe kidney, who presented with hematuria and was successfully treated with endovascular embolization. The use of a microballoon catheter Scepter XC (Microvention, Inc.) to safely embolize the feeding arterial supply, using ethylene vinyl alcohol (EVOH) copolymer (Onyx; Medtronic/ev3) has not, to the authors’ knowledge, previously been described for the treatment of renal AVM. This novel use of an occlusal balloon catheter is permitted by the precipitation rate of Onyx, and allowed a safe and effective procedure, reducing the risk of reflux, allowing a forward push of embolic material in a controlled manner.
Keywords: renal intervention; arteriovenous malformation; microballoon catheter Scepter XC